Effects of Furrow Irrigation on the Growth, Production, and Water Use Efficiency of Direct Sowing Rice - Chunlin He (The Scientific World Journal)
Rice farming is the major crop production in Asia and is predicted to increase significantly in the near future in order to meet the demands for the increasing human population. Traditional irrigation methods used in rice farming often result in great water loss. New water-saving methods are urgently needed to reduce water consumption. Three field and pot experiments were conducted to evaluate the furrow irrigation (FI) system to improve water use efficiency (WUE) and production of direct sowing rice in southern China. Compared to the conventional irrigation (CI) system (continuous flooding irrigation), for every square hectometer of rice field, the FI system reduced water use by 3130 m3, or 48.1%, and increased grain production by 13.9% for an early cultivar. For a late cultivar, the FI system reduced water use by 2655 m3, or 40.6%, and an increase of grain production by 12.1%. The improved WUE in the FI system is attributed to (1) a significant reduction of irrigation rate, seepage, evaporation, and evapotranspiration; (2) a significant reduction in the reduced materials, such as ferrous ion (Fe2+), and therefore an increase in the vitality of the root system, evident by the increases in the number of white roots by 32.62%, and decreases in the number of black roots by 20.04% and yellow roots by 12.58%; the use of the FI system may also reduce humidity of the rice field and enhance gas transport in the soil and light penetration, which led to reduced rice diseases and increased leaf vitality; and (3) increases in tiller and effective spikes by 11.53% and the weight per thousand grains by 1.0 g. These findings suggest that the shallow FI system is a promising means for rice farming in areas with increasing water shortages.